2014
DOI: 10.1111/trf.12756
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the freezing process for hematopoietic progenitor cells: effect of precooling, initial dimethyl sulfoxide concentration, freezing program, and storage in vapor‐phase or liquid nitrogen on in vitro white blood cell quality

Abstract: Based on these results, precooling is not necessary. Fifty percent D/P is preferred over 20% D/P. Slow-rate freezing is preferred over fast-rate freezing. For safety reasons storage in vapor-phase nitrogen is preferred over storage in liquid nitrogen. Additional testing using real HPCs might be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Dijkstra-Tiekstra et al [60] performed a study using precooled DMSO and precooled white blood cells (WBCs). Results showed that precooling has a minimal effect on WBC recovery.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Dijkstra-Tiekstra et al [60] performed a study using precooled DMSO and precooled white blood cells (WBCs). Results showed that precooling has a minimal effect on WBC recovery.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Current methods of optimizing cryopreservation solutions most often use empirical methods, by testing a given composition and cooling rate and measuring post‐thaw recovery (Conrad et al ., ; Dijkstra‐Tiekstra et al ., ; Dong et al ., ; Freimark et al ., ; Kearney et al , ). Our studies show that optimization of freezing solutions can be performed using a DE algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Freezing solution composition also influences cell survival (Mazur, ), and changing the composition of the cryopreservation solution may change the cooling rate at which optimum survival is observed. Cryopreservation protocols are most often determined empirically by changing the composition and cooling rate until the desired outcome is obtained (Conrad et al ., ; Dijkstra‐Tiekstra et al ., ; Dong et al ., ; Freimark et al ., ; Kearney et al , ). This process is typically expensive, time‐consuming and may not result in an optimized protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Sputtek et al [87] reported that the cooling rate range can vary from 1 to 5 K/ min. Also, the recovery of white blood cell (WBC) recovery was found to be superior in slow rate freezing to fast rate freezing [88]. After the introduction of stem cell storage in liquid nitrogen, risks for microbial contamination of the products concluded with the usage of vapor phase for storage.…”
Section: Hematopoietic Progenitor Cell and Umbilical Cord Blood Cryopmentioning
confidence: 99%